Designing The Model Of Meaning-Based Tarannum Mobile Application In Kelas Khas Kemahiran Membaca Dan Menghafaz Al-Quran (KKQ) - Nurul Auji Binti Hasbullah
Tarannum is one of the subjects taught at the secondary school level in Special Class of Reading and Memorizing of the Qur’ān (KKQ). The KKQ classes were limited to only selected schools under the Ministry of Education (MoE) such as Sekolah Menengah Kebangsaan Agama (SMKA), Sekolah Berasrama Penuh (SBP) and Sekolah Menengah Kebangsaan which have religious stream class (SMK KAA). Several issues and problems have been identified which are related to the issue of the KKQ class. One of the highlighted issues is the problems that are related to teaching and learning aids. Therefore, the main objective of this study is to design a model of KKQ Tarannum learning that are integrated with mobile technology by emphasising the understanding of Qur’ānic verses as the best practice in reciting Al-Qur’ān with Tarannum. This study was conducted based on the Design and Development Research (DDR) approach by Richey and Klein that comprises of three phases namely phase 1: the analysis phase, phase 2: the design and development phase and phase 3: the evaluation phase. For phase 1, the objective of the study is to analyse the needs in developing KKQ Tarannum model based on the meaning of Qur’ān verses. The method used in this phase is the document analysis and also the interviews with participants, namely KKQ teachers, students and also qāri’ and qāri’ah. As for the research instrument, the interview protocol was used. The sample of this phase uses purposive sampling method to ensure that the findings obtained are accurate and valid. The findings of the study were analysed by using ATLAS.ti and the data were analysed thematically. The findings from phase 1 were several issues and problems related to the field of Tarannum discovered and there is a need to develop a Tarannum mobile application for the KKQ class. For phase 2, the objective of the study was to design and develop a KKQ meaning-based Tarannum mobile application model. The method used was document analysis from the existing Tarannum mobile app as well as the KKQ handbook. Matrix analysis was developed and used to look at the components, elements as well as features of the existing Tarannum mobile app. The data were analysed thematically and the findings for phase 2 is a prototype model of the KKQ meaning-based Tarannum mobile app. For phase 3, the objective of the study was to evaluate the KKQ meaning-based Tarannum mobile app model with the experts. The method used in this expert evaluation is by using Fuzzy Delphi method whereby the expert questionnaire was constructed as research instrument based on model prototype in phase 2. The data was analysed by using a Fuzzy Delphi template in Microsoft excel. The result of the findings from this phase is the final model of KKQ meaning-based Tarannum mobile application after obtaining the expert agreement. This study has given implications to the methodology, theory and model of the study whereby a systematic study has been conducted based on the DDR approach and has produced a model which integrates the Tarannum meaning-based theory and constructivism theory. This study is conducted to enhance the learning outcome for this Tarannum subject through the learning model in a form of mobile applications (mobile app) which is an active and constructive learning whereby it can be used as teaching and learning aids everywhere and at any time.